The combined effects of the cooling rate and alloying element on the mechanical behavior of Mg-Mn-Zn alloying system - Jamel, Murtatha M.; Lopez, Hugo; Cho, Emilee; Lindner, Brad (Journal of Alloys and Metallurgical Systems, 2024)
Magnesium (Mg) alloys have recently been the subject of many investigations, as they show great potential for use in a multitude of applications. Due to their biocompatibility and attractive mechanical properties, one of the areas showing the greatest potential is with orthopedic biomedical implants. Because the suitability of implant devices hinges greatly on their ability to mimic bone, the mechanical properties are of paramount importance when it comes to material selection. The goal of this study was to produce a biodegradable-biomedical alloy with desired mechanical properties. Since Mg is a biodegradable and biomedical alloy, it became the starting point for the alloying system. However, Mg lacks some desired mechanical properties, so the study aimed to improve the mechanical properties to be suitable for such applications. This work investigates the influence of different cooling rates on the strength of pure Mg. Additionally, the influence in adding zinc (Zn) and manganese (Mn) to create Mg-1Mn-2Zn and Mg-1Mn-4Zn alloys were studied. Hardness, tensile, and impact testing were performed in addition to fractography and microstructural evaluations. All chemical compositions were illustrated as a weight percent, or wt%. It was found that in general, for both the pure magnesium and Mg-Mn-Zn alloys, the mechanical properties had a tendency to improve by refinement of the grain structure.